Ethics in Plastic Surgery: Applying the Four Common Principles to Practice. Issue 3 (September 2018) - Gallo, Lucas; Baxter, Charmaine; Murphy, Jessica; Schwartz, Lisa; Thoma, Achilleas
Abstract : Summary: The topic of ethics in plastic surgery remains underrepresented in the literature. By applying the four principles of biomedical ethics—respect for autonomy, beneficence, nonmaleficence, and justice—as described by Beauchamp and Childress to proposed ethical scenarios, this article attempts to provide plastic surgeons with a systematic approach to recognize and address ethical dilemmas as they present in day-to-day practice. Through the perspective of an experienced plastic surgeon and medical ethicist, this article is intended to spark discussion, reflection, and debate on ethical challenges in plastic surgery.